Prefibrotic Myelofibrosis Presenting with Multiple Cerebral Embolic Infarcts and the Rare MPL W515S Mutation - Stephen E. Langabeer; Lisa Lee Tokar; Laura Kearney; Cathal O’Brien; Kowshika Thavarajah; Aisling Barrett; John McManus; Hilary O’Leary (Case Reports in Hematology)
Acquired, activating mutations of MPL W515 are recognised driver mutations of the myeloproliferative neoplasms (MPN), namely, essential thrombocythemia and primary myelofibrosis. The most common mutation at this codon is W515L with several other mutations also described at a lower frequency. Of these less common mutations, MPL W515S has only been reported sporadically with limited information on clinicopathological associations. We describe the case of an elderly man with persistent thrombocytosis presenting with an ischemic cerebral event. Bone marrow biopsy showed evidence of prefibrotic myelofibrosis with targeted sequencing demonstrating the presence of the rare MPL W515S mutation. Thrombolytic and cytoreductive therapies resulted in a favorable outcome and follow-up. This case provides additional, necessary, and phenotypic data for the rare MPN-associated MPL W515S mutation.